DETERMINANT FACTORS OF EXCLUSIVE BREAST MILK IN PANGGUNGHARJO VILLAGE - Reni Maelani; Lina Handayani; Sitti Nur Djannah (Jurnal Kesehatan, 2022)
The low level of breastfeeding is a threat to the growth and development of children which will affect the growth and development of the quality of human resources in general. This study aims to determine the relationship between knowledge, attitude, self-confidence and husband's support with exclusive breastfeeding in the Panggungharjo Village area. This research design is correlational with cross sectional approach method. The population in this study were 34 mothers who had babies aged 6-24 months in Panggungharjo Village, Bantul Regency, Yogyakarta Special Region Province. The samples taken in this study were mothers who lived in the Panggungharjo Village area who had babies aged 6 -24 months. Data were analyzed by chi-square analysis. The results showed that knowledge (p-value 0.000 (<0.05)), attitude (p-value 0, 039 (<0.05)), self-confidence (p-value 0.030 (<0.05)) and husband's support (p-value 0.005 (<0.05)) are variables related to exclusive breastfeeding in Panggungharjo Village. Conclusion: Knowledge, attitude, self-confidence and support from husbands of breastfeeding mothers are the determinants of exclusive breastfeeding in Panggungharjo Village.